2013
DOI: 10.1186/2050-6511-14-48
|View full text |Cite
|
Sign up to set email alerts
|

The favorable kinetics and balance of nebivolol-stimulated nitric oxide and peroxynitrite release in human endothelial cells

Abstract: BackgroundNebivolol is a third-generation beta-blocker used to treat hypertension. The vasodilation properties of nebivolol have been attributed to nitric oxide (NO) release. However, the kinetics and mechanism of nebivolol-stimulated bioavailable NO are not fully understood.MethodsUsing amperometric NO and peroxynitrite (ONOO-) nanosensors, β3-receptor (agonist: L-755,507; antagonists: SR59230A and L-748,337), ATP efflux (the mechanosensitive ATP channel blocker, gadolinium) and P2Y-receptor (agonists: ATP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Nebivolol was also found to increase NO release in cultured endothelial cells and isolated arteries . The stimulatory effect of nebivolol may be mediated through β 2 ‐ or β 3 ‐receptors . Oral nebivolol in combination with bendroflumethiazide for 8 weeks increased both basal and stimulated endothelium‐derived NO estimated by forearm venous occlusion plethysmography and intra‐arterial infusions of acetylcholine and L‐NMMA .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nebivolol was also found to increase NO release in cultured endothelial cells and isolated arteries . The stimulatory effect of nebivolol may be mediated through β 2 ‐ or β 3 ‐receptors . Oral nebivolol in combination with bendroflumethiazide for 8 weeks increased both basal and stimulated endothelium‐derived NO estimated by forearm venous occlusion plethysmography and intra‐arterial infusions of acetylcholine and L‐NMMA .…”
Section: Discussionmentioning
confidence: 92%
“…In vitro incubation of isolated vessels and in vivo infusion in forearm vasculature with nebivolol was found to induce vasodilatation, which could be blocked by inhibition of NO synthesis . Nebivolol was also found to increase NO release in cultured endothelial cells and isolated arteries . The stimulatory effect of nebivolol may be mediated through β 2 ‐ or β 3 ‐receptors .…”
Section: Discussionmentioning
confidence: 96%
“…. The same group quantified PON after release upon stimulation by a beta-blocker medication, Nebivolol(135) as illustrated in inset (G).…”
mentioning
confidence: 98%
“…[2][3][4][5] It is a racemic mixture of D-and L-enantiomers, of which D-nebivolol is considered to be a highly selective b-adrenergic receptor antagonist. [5][6][7][8] It was demonstrated that nebivolol stimulates NO release through both b 3 -receptor and adenosine triphosphate-dependent, P2Y-receptor activation.…”
mentioning
confidence: 99%
“…[5][6][7][8] It was demonstrated that nebivolol stimulates NO release through both b 3 -receptor and adenosine triphosphate-dependent, P2Y-receptor activation. 3,[9][10][11][12] In a well-designed clinical study, Tzemos and coworkers 13 analyzed whether nebivolol could improve endothelial dysfunction in patients with essential hypertension. They showed that nebivolol/bendrofluazide increased both stimulated and basal endothelial NO release, whereas, for the same degree of blood pressure control, atenolol/bendrofluazide had no effect on NO bioactivity; therefore, they concluded that nebivolol may offer additional vascular protection in treating hypertension.…”
mentioning
confidence: 99%